Respuesta :

tonb
You can just add the terms:

(-x^2+9)+(-3x^2-11x+4) = -4x² - 11x + 13

Answer:

[tex]-4x^{2} -11x+13[/tex]

Step-by-step explanation:

Step to add the integers.

When we add two positive integers,we add integers  and +sign is used.

When we dd two positive integers, we add subtract integers, and greater integer  sign is used.

When we add two negative integer, we add integers  and -sign is used.

=([tex]-x^{2} +9^{}[/tex])+([tex]-3x^{2} -11x^{} +4^{}[/tex])  

=[tex]-x^{2} +9-3x^{2} -11x+4[/tex]

=[tex]-x^{2} -3x^{2} -11x+9+4[/tex]

=[tex]-4x^{2} -11x+9+4[/tex]

=[tex]-4x^{2} -11x+13[/tex]